The All-Sky Automated Search for Supernovæ Going Global: Poster on-line. Issue Volume 14:Issue S339(2018) (November 2017) - Stritzinger, M.
Abstract: The All-Sky Automated-Survey for SuperNovæ (ASAS-SN) is a fully automated transient search programme that is currently observing the entire night sky every second night to a depth of about 18 th magnitude. Since becoming on-line in mid-2014, ASAS-SN has discovered over half of all bright supernovæ, and along the way has also discovered numerous tidal disruption events, cataclysmic variables, stellar flares and even a comet! ASAS-SN currently has two units deployed between Chile and Hawaii, and an additional three units were slated to come on-line by the end of 2017 at observatories in South Africa, Chile and Texas. The poster provided a brief summary of ASAS-SNs accomplishments, and discussed future prospects based on its global expansion.